Water-based coating composition for battery diaphragm and preparation method of water-based coating composition
By using an aqueous coating composition in a lithium-ion battery separator, combining copolymer amine salt olefin resin, modified glass fiber and adjusting stabilizer, the adhesion and stability of existing coatings are solved, and excellent Insulation and heat resistance, suitable for large-scale production and long-term storage.
Patent Information
- Application Number
- CN202411325639.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-ion battery separator coatings have problems with poor adhesion, heat resistance and circulation performance due to the use of organic solvents and polymer aqueous emulsions, and have poor stability in storage and large-scale production, resulting in impurities generation and flocculation. Reunion phenomenon.
The aqueous coating composition, including copolymer amine salt olefin resin as binder, modified glass fiber and adjustable stabilizer as modified additives, form strong hydrogen bonds and multi-point linear support through specific preparation methods, Titanium dioxide is chimeric to enhance insulation and heat resistance and optimize the stability of the composition by ball milling and blending treatment.
Excellent adhesion, insulation, heat resistance and cycling performance are achieved, while reducing settlement and flocculation in long-term storage, suitable for large-scale production, and significantly improving the stability and performance of the coating composition.
Smart Images

Figure BDA0005055337970000131 
Figure BDA0005055337970000141
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery separators, and in particular to an aqueous coating composition for battery separators and a preparation method thereof. Background Art
[0002] As traditional resources and energy become increasingly scarce and environmental problems become increasingly serious, sustainable development has become a new concept for the development of human society, and the development of new energy storage and conversion technologies has become the focus of energy strategies in various countries. Lithium-ion batteries have become the technology with the greatest development potential in the new era due to their high energy density, high operating voltage, long cycle life, and low self-discharge.
[0003] In order to improve the production efficiency of batteries, a coating with good adhesion to the diaphragm and good cycle performance has been proposed. However, the existing commonly used coatings are oily systems, using PVDF, styrene-butadiene rubber, nitrile rubber, etc. as binders, and using organic solvents such as NMP and toluene, which are highly toxic to the environment and human body. Other types of coatings use polymer water-based emulsions, which will also cause impurities and poor stability during the use and storage of lithium batteries due to residual emulsifiers and initiators and other chemical substances.
[0004] Therefore, in order to solve the above problems, the present application provides an aqueous coating composition for battery separators and a preparation method thereof, which can ensure excellent adhesion, heat resistance and cycle performance while also having its own stability in long-term storage and large-scale production. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides an aqueous coating composition for a battery separator, wherein the raw materials include, by weight: 15 to 25 parts of a binder, 1 to 10 parts of a swelling agent, 10 to 30 parts of a modifying additive, 0.5 to 5 parts of a cross-linking agent, 1 to 10 parts of an auxiliary agent, and deionized water is added to 100 parts;
[0006] The binder is a copolymer amine salt olefin resin;
[0007] The copolymer amine salt olefin resin is at least one of ethylene-acrylic acid copolymer amine salt, styrene-ethylene-acrylic acid copolymer amine salt, styrene-acrylic acid-maleic anhydride copolymer amine salt, ethylene-methacrylic acid copolymer amine salt, and styrene-acrylic acid copolymer amine salt;
[0008] The swelling agent is polyvinyl pyrrolidone or acrylic acid-vinyl pyrrolidone copolymer.
[0009] As a preferred solution, the modified additive is a composition of modified glass fiber and a regulating and stabilizing agent; wherein the mass ratio of the modified glass fiber to the regulating and stabilizing agent is 7:(2-4);
[0010] The preparation method of the modified glass fiber comprises the following steps:
[0011] S1: 2-5 parts of urea, 1-3 parts of silane coupling agent KH560 and 4-7 parts of 10% by mass dodecylbenzene sulfonic acid solution are mixed to form a modified solution, 3-6 parts of titanium dioxide are added to the modified solution and stirred for modification treatment, the modification speed is 450-500r / min, the modification time is 1-2h, the modification temperature is 45-50°C, the modification is completed, washed with water, and dried to obtain modified titanium dioxide;
[0012] S2: Dissolve 4-7 parts of succinic anhydride in 15-20 parts of DMF solvent, add 1-2 parts of (3-aminopropyl)triethoxysilane, then add 3-5 parts of modified titanium dioxide, heat and stir at a water bath temperature of 80-95°C for 1-2 hours, then cool to 60-70°C and keep warm for 2-3 hours, and collect the precipitate by centrifugation and washing;
[0013] S3: Add the precipitate to a sufficient amount of ethanol, then add glass fiber, raise the temperature to 50-60°C, and stir in a water bath ultrasonic manner at a speed of 200-300 r / min and a power of 200-400 W for 3-4 hours, then centrifuge and wash, and vacuum dry at 60°C.
[0014] As a preferred solution, the mass ratio of the precipitate to the glass fiber is (1-2): (8-12);
[0015] The average length of the glass fibers is 1 to 3 μm.
[0016] As a preferred solution, the preparation method of the regulating stabilizer comprises the following steps:
[0017] S11: add 6-10 parts of bentonite to 25-30 parts of DMF solvent, perform water bath ultrasound at 100-200w for 1-2h, then add 1-3 parts of toluenesulfonic acid, raise the temperature to 50-60°C, and keep warm for 2-3h;
[0018] S12; The product is washed by centrifugation and added to 15-20 parts of methanol, and 4-6 parts of dimethylimidazole and 2-4 parts of gas-phase alumina are added at the same time. The temperature is raised to 60-65°C and the reaction is carried out for 1.5-2h. After completion, the product is filtered and dried.
[0019] As a preferred solution, the preparation method of the bentonite agent is:
[0020] The bentonite is first heated to 155-165°C at a rate of 1-3°C / min, kept warm for 5-10 minutes, then heated to 210-230°C at a rate of 2-5°C / min, kept warm for 2 minutes, and finally air-cooled to room temperature. 5-10 parts of air-cooled room temperature bentonite, 2-5 parts of yttrium nitrate solution, 1-3 parts of carboxymethyl cellulose and 2-4 parts of chitosan solution are blended and ball-milled thoroughly. The ball-milling speed is 1000r / min. The ball-milling is carried out for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a bentonite agent.
[0021] As a preferred solution, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the chitosan solution is 6%.
[0022] As a preferred solution, the cross-linking agent is pentaerythritol-tris(3-aziridinyl)propionate.
[0023] As a preferred solution, the auxiliary agents are a defoamer and a dispersant; the mass ratio of the defoamer to the dispersant is 1:1; the defoamer is BYK-019; and the dispersant is PEG-800.
[0024] The second aspect of the present application provides a method for preparing an aqueous coating composition for a battery separator, and the preparation method comprises the following steps: S1: adding a binder to deionized water and stirring evenly until there is no obvious floc; S2: then adding a modifying additive, a swelling agent, a cross-linking agent and an auxiliary agent to the above-mentioned S1 solution in sequence, stirring and mixing evenly, and ball-milling it thoroughly to obtain an aqueous coating composition for a battery separator.
[0025] Beneficial effects:
[0026] The present application provides an aqueous coating composition for battery separators, which not only has excellent adhesion, insulation, heat resistance and cycle performance, but also has better self-stability than the coating composition of the prior art, and can effectively reduce the sedimentation, precipitation and flocculation and agglomeration of the coating composition during long-term storage, which is greatly beneficial to the storage requirements of the coating composition during large-scale production;
[0027] In the present application, by adopting the modified glass fiber mentioned above, it is possible to effectively ensure that the coating composition has excellent insulation, heat resistance, coating stability and cycle stability. This is mainly because, in the present application, the modified glass fiber mentioned above can exist as a linear support at multiple points in the coating composition. After the treatment of the modified titanium dioxide, it can be firmly embedded in the gaps between the glass fibers, and through the multi-hydroxyl groups on its surface, it forms strong hydrogen bonds with other raw materials in the coating composition, thereby enhancing its system support in the coating and the cured coating. At the same time, the presence of a large amount of embedded titanium dioxide can form a linear structure supported by multiple particle points at the same time when the coating is subjected to external forces and expansion, thereby greatly reducing the influence of external forces and expansion on the structure and volume of the coating; on the other hand, in the coating composition, the attraction between the embedded titanium dioxide can also promote the glass fiber to reinforce the system structure in the system, intersperse the system, enhance the insulation dielectric properties of the system, and the capacity cycle stability of the product;
[0028] At the same time, an adjusting stabilizer is used in conjunction with the modified glass fiber. Through the synergistic effect of the two, the strength of the internal network structure of the coating composition during storage is stabilized, thereby playing a strong supporting role and avoiding precipitation, agglomeration and the like during storage, thereby significantly improving the performance of the product; the adjusting stabilizer uses a bentonite agent in conjunction with the modification process of the present invention to optimize the product performance effect. The bentonite agent uses bentonite to first heat the temperature to 155-165°C at a rate of 1-3°C / min, keep warm for 5-10 minutes, then heat the temperature to 210-230°C at a rate of 2-5°C / min, continue to keep warm for 2 minutes, and finally air-cool to room temperature to optimize the interlayer spacing of the bentonite sheets, thereby improving the sheet accommodation and the improved effect of the coordinated matching of the product raw materials, thereby enhancing the performance stability of the system in the system, and at the same time, after being blended and ball-milled with yttrium nitrate solution, carboxymethyl cellulose and chitosan solution, the synergistic effect between the raw materials is further enhanced, thereby further improving the product performance. DETAILED DESCRIPTION
[0029] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0030] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0031] Example 1
[0032] The aqueous coating composition for a battery separator of this embodiment comprises, by weight, 15 parts of a binder, 1 part of a swelling agent, 10 parts of a modifying additive, 0.5 parts of a cross-linking agent, 1 part of an auxiliary agent, and deionized water to make up to 100 parts;
[0033] The binder is a copolymer amine salt olefin resin;
[0034] The copolymer amine salt olefin resin is an ethylene-acrylic acid copolymer amine salt;
[0035] The swelling agent is polyvinyl pyrrolidone;
[0036] As a preferred solution, the modified additive is a composition of modified glass fiber and a regulating and stabilizing agent; wherein the mass ratio of the modified glass fiber to the regulating and stabilizing agent is 7:2;
[0037] The preparation method of the modified glass fiber comprises the following steps:
[0038] S1: 2 parts of urea, 1 part of silane coupling agent KH560 and 4 parts of 10% by mass dodecylbenzene sulfonic acid solution are mixed to form a modified solution, 3 parts of titanium dioxide are added to the modified solution and stirred for modification treatment, the modification speed is 450r / min, the modification time is 1h, the modification temperature is 45°C, the modification is completed, washed with water, and dried to obtain modified titanium dioxide;
[0039] S2: Dissolve 4 parts of succinic anhydride in 15 parts of DMF solvent, add 1 part of (3-aminopropyl)triethoxysilane, then add 3 parts of modified titanium dioxide, heat and stir at a water bath temperature of 80°C for 1 hour, then cool to 60°C and keep warm for 2 hours, and collect the precipitate by centrifugation and washing;
[0040] S3: Add the precipitate to a sufficient amount of ethanol, then add glass fiber, raise the temperature to 50°C, and stir in a water bath ultrasonically at a speed of 200 r / min and a power of 200 W for 3 hours, then centrifuge and wash, and vacuum dry at 60°C.
[0041] The mass ratio of precipitate to glass fiber is 1:8;
[0042] The average length of the glass fibers was 1 μm.
[0043] The preparation method of the stabilizer comprises the following steps:
[0044] S11: 6 parts of bentonite were added to 25 parts of DMF solvent, and ultrasonicated in a water bath at 100W for 1 hour, and then 1 part of toluenesulfonic acid was added, and the temperature was raised to 50°C and kept warm for 2 hours;
[0045] S12; The product was washed by centrifugation and added to 15 parts of methanol, and 4 parts of dimethylimidazole and 2 parts of gas-phase alumina were added at the same time. The temperature was raised to 60°C and the reaction was carried out for 1.5 hours. After completion, the product was filtered and dried.
[0046] The preparation method of bentonite is as follows:
[0047] The bentonite was first heated to 155°C at a rate of 1°C / min, kept warm for 5 minutes, then heated to 210°C at a rate of 2°C / min, kept warm for 2 minutes, and finally air-cooled to room temperature. 5 parts of air-cooled room temperature bentonite, 2 parts of yttrium nitrate solution, 1 part of carboxymethyl cellulose and 2 parts of chitosan solution were blended and ball-milled thoroughly. The ball-milling speed was 1000r / min, and the ball-milling was carried out for 1 hour. After the ball-milling was completed, the mixture was washed with water and dried to obtain a bentonite agent.
[0048] The mass fraction of the yttrium nitrate solution is 2%; the mass fraction of the chitosan solution is 6%.
[0049] The crosslinking agent is pentaerythritol-tris(3-aziridinyl)propionate.
[0050] As a preferred solution, the auxiliary agents are a defoamer and a dispersant; the mass ratio of the defoamer to the dispersant is 1:1; the defoamer is BYK-019; and the dispersant is PEG-800.
[0051] The second aspect of the present application provides a method for preparing an aqueous coating composition for a battery separator, and the preparation method comprises the following steps: S1: adding a binder to deionized water and stirring evenly until there is no obvious floc; S2: then adding a modifying additive, a swelling agent, a cross-linking agent and an auxiliary agent to the above-mentioned S1 solution in sequence, stirring and mixing evenly, and ball-milling it to obtain an aqueous coating composition for a battery separator.
[0052] Example 2
[0053] The aqueous coating composition for a battery separator of this embodiment comprises, by weight, 25 parts of a binder, 10 parts of a swelling agent, 30 parts of a modifying additive, 5 parts of a cross-linking agent, 10 parts of an auxiliary agent, and deionized water to 100 parts.
[0054] The binder is a copolymer amine salt olefin resin;
[0055] The copolymer amine salt olefin resin is a styrene-ethylene-acrylic acid copolymer amine salt;
[0056] The swelling agent is polyvinyl pyrrolidone or acrylic acid-vinyl pyrrolidone copolymer;
[0057] As a preferred solution, the modified additive is a composition of modified glass fiber and a regulating and stabilizing agent; wherein the mass ratio of the modified glass fiber to the regulating and stabilizing agent is 7:4;
[0058] The preparation method of the modified glass fiber comprises the following steps:
[0059] S1: 5 parts of urea, 3 parts of silane coupling agent KH560 and 7 parts of 10% by mass dodecylbenzene sulfonic acid solution are mixed to form a modified solution, 6 parts of titanium dioxide are added to the modified solution and stirred for modification treatment, the modification speed is 500r / min, the modification time is 2h, the modification temperature is 50°C, the modification is completed, washed with water, and dried to obtain modified titanium dioxide;
[0060] S2: Dissolve 7 parts of succinic anhydride in 20 parts of DMF solvent, add 2 parts of (3-aminopropyl)triethoxysilane, then add 5 parts of modified titanium dioxide, heat and stir at a water bath temperature of 95°C for 2 hours, then cool to 70°C and keep warm for 3 hours, and collect the precipitate by centrifugation and washing;
[0061] S3: Add the precipitate to a sufficient amount of ethanol, then add glass fiber, heat to 60°C, stir in a water bath with ultrasonic at 300 r / min and 400 W for 4 h, then centrifuge and wash, and dry in a vacuum oven at 60°C.
[0062] The mass ratio of precipitate to glass fiber is 2:12;
[0063] The average length of the glass fibers was 3 μm.
[0064] The preparation method of the stabilizer comprises the following steps:
[0065] S11: 10 parts of bentonite were added to 30 parts of DMF solvent, and ultrasonicated in a water bath at 200W for 2 hours, and then 3 parts of toluenesulfonic acid were added, and the temperature was raised to 60°C and kept warm for 3 hours;
[0066] S12; The product is washed by centrifugation and added to 20 parts of methanol, and 6 parts of dimethylimidazole and 4 parts of gas-phase alumina are added at the same time, and the temperature is raised to 65°C, and the reaction is carried out for 2 hours. After completion, the product is filtered and dried.
[0067] The preparation method of bentonite is as follows:
[0068] The bentonite was first heated to 165°C at a rate of 3°C / min, kept warm for 10 minutes, then heated to 230°C at a rate of 5°C / min, kept warm for 2 minutes, and finally air-cooled to room temperature. 10 parts of air-cooled room temperature bentonite, 5 parts of yttrium nitrate solution, 3 parts of carboxymethyl cellulose and 4 parts of chitosan solution were blended and ball-milled thoroughly. The ball-milling speed was 1000r / min, and the ball-milling was carried out for 1 hour. After the ball-milling was completed, the mixture was washed with water and dried to obtain a bentonite agent.
[0069] The mass fraction of the yttrium nitrate solution is 5%; the mass fraction of the chitosan solution is 6%.
[0070] The crosslinking agent is pentaerythritol-tris(3-aziridinyl)propionate.
[0071] As a preferred solution, the auxiliary agents are a defoamer and a dispersant; the mass ratio of the defoamer to the dispersant is 1:1; the defoamer is BYK-019; and the dispersant is PEG-800.
[0072] The second aspect of the present application provides a method for preparing an aqueous coating composition for a battery separator, and the preparation method comprises the following steps: S1: adding a binder to deionized water and stirring evenly until there is no obvious floc; S2: then adding a modifying additive, a swelling agent, a cross-linking agent and an auxiliary agent to the above-mentioned S1 solution in sequence, stirring and mixing evenly, and ball-milling it to obtain an aqueous coating composition for a battery separator.
[0073] Example 3
[0074] The aqueous coating composition for a battery separator of this embodiment comprises, by weight, 20 parts of a binder, 5 parts of a swelling agent, 20 parts of a modifying additive, 2 parts of a cross-linking agent, 5 parts of an auxiliary agent, and deionized water to 100 parts.
[0075] The binder is a copolymer amine salt olefin resin;
[0076] The copolymer amine salt olefin resin is an ethylene-acrylic acid copolymer amine salt;
[0077] The swelling agent is polyvinyl pyrrolidone or acrylic acid-vinyl pyrrolidone copolymer;
[0078] As a preferred solution, the modified additive is a composition of modified glass fiber and a regulating and stabilizing agent; wherein the mass ratio of the modified glass fiber to the regulating and stabilizing agent is 7:3;
[0079] The preparation method of the modified glass fiber comprises the following steps:
[0080] S1: 3.5 parts of urea, 2 parts of silane coupling agent KH560 and 5.5 parts of 10% by mass dodecylbenzene sulfonic acid solution are mixed to form a modified liquid, 4.5 parts of titanium dioxide are added to the modified liquid and stirred for modification treatment, the modification speed is 470r / min, the modification time is 1.5h, the modification temperature is 47°C, the modification is completed, washed with water, and dried to obtain modified titanium dioxide;
[0081] S2: Dissolve 5.5 parts of succinic anhydride in 17 parts of DMF solvent, add 1.5 parts of (3-aminopropyl)triethoxysilane, then add 4 parts of modified titanium dioxide, heat and stir at a water bath temperature of 85°C for 1.5 hours, then cool to 65°C and keep warm for 2.5 hours, and collect the precipitate by centrifugation and washing;
[0082] S3: Add the precipitate to a sufficient amount of ethanol, then add glass fiber, heat to 55°C, stir in a water bath with ultrasonic at 250 r / min and 300 W for 3.5 h, then centrifuge and wash, and vacuum dry at 60°C.
[0083] The mass ratio of precipitate to glass fiber is 1.5:9;
[0084] The average length of the glass fibers was 2 μm.
[0085] The preparation method of the stabilizer comprises the following steps:
[0086] S11: 8 parts of bentonite were added to 28 parts of DMF solvent, and ultrasonicated in a water bath at 150W for 1.5 hours. Then, 2 parts of toluenesulfonic acid were added, and the temperature was raised to 55°C and kept warm for 2.5 hours.
[0087] S12; The product was washed by centrifugation and added to 17.5 parts of methanol, and 5 parts of dimethylimidazole and 3 parts of gas-phase alumina were added at the same time. The temperature was raised to 62°C and the reaction was carried out for 1.7 hours. After completion, the product was filtered and dried.
[0088] The preparation method of bentonite is as follows:
[0089] The bentonite was first heated to 160°C at a rate of 2°C / min, kept warm for 7.5 min, then heated to 220°C at a rate of 3.5°C / min, kept warm for 2 min, and finally air-cooled to room temperature. 7.5 parts of air-cooled room temperature bentonite, 3.5 parts of yttrium nitrate solution, 2 parts of carboxymethyl cellulose and 3 parts of chitosan solution were blended and ball-milled thoroughly. The ball-milling speed was 1000 r / min, and the ball-milling was carried out for 1 h. After the ball-milling was completed, the mixture was washed with water and dried to obtain a bentonite agent.
[0090] The mass fraction of the yttrium nitrate solution is 3.5%; the mass fraction of the chitosan solution is 6%.
[0091] The crosslinking agent is pentaerythritol-tris(3-aziridinyl)propionate.
[0092] As a preferred solution, the auxiliary agents are a defoamer and a dispersant; the mass ratio of the defoamer to the dispersant is 1:1; the defoamer is BYK-019; and the dispersant is PEG-800.
[0093] The second aspect of the present application provides a method for preparing an aqueous coating composition for a battery separator, and the preparation method comprises the following steps: S1: adding a binder to deionized water and stirring evenly until there is no obvious floc; S2: then adding a modifying additive, a swelling agent, a cross-linking agent and an auxiliary agent to the above-mentioned S1 solution in sequence, stirring and mixing evenly, and ball-milling it to obtain an aqueous coating composition for a battery separator.
[0094] Comparative Example 1
[0095] The specific implementation of this comparative example is basically the same as that of Example 3, except that no modified glass fiber is added to the modified additive.
[0096] Comparative Example 2
[0097] The specific implementation of this comparative example is basically the same as that of Example 3, except that no modified titanium dioxide is added in the modification of the modified glass fiber.
[0098] Comparative Example 3
[0099] The specific implementation of this comparative example is basically the same as that of Example 3, except that the modified titanium dioxide is replaced by titanium dioxide.
[0100] Comparative Example 4
[0101] The specific implementation of this comparative example is basically the same as that of Example 3, except that no regulating stabilizer is added to the modifying additive.
[0102] Comparative Example 5
[0103] The specific implementation method of this comparative example is basically the same as that of Example 3, except that no bentonite agent is added in the preparation of the regulating stabilizer.
[0104] Comparative Example 6
[0105] The specific implementation method of this comparative example is basically the same as that of Example 3, except that: in the preparation of the bentonite agent, the temperature is not first raised to 160°C at a rate of 2°C / min, kept warm for 7.5 minutes, then raised to 220°C at a rate of 3.5°C / min, kept warm for 2 minutes, and finally air-cooled to room temperature.
[0106] Comparative Example 7
[0107] The specific implementation of this comparative example is basically the same as that of Example 3, except that: the yttrium nitrate solution, 2 parts of carboxymethyl cellulose and 3 parts of chitosan solution were not blended and ball-milled in the preparation of the bentonite agent.
[0108] Performance Evaluation
[0109] Coating storage stability: Samples of the coating compositions prepared in the embodiments and comparative examples were taken, added to a constant temperature box, set at a temperature of 50°C and a humidity of 75%, and observed for 14 days. If obvious sedimentation and flocculation of the coating composition occurred before 14 days, it was determined to be unqualified; otherwise, if the above conditions did not occur for more than 14 days, it was determined to be qualified. 100 samples were tested for each embodiment and comparative example, and the qualified rate of the 100 samples was calculated, qualified rate (%) = number of qualified samples / 100 × 100%.
[0110] Peel strength after immersion in electrolyte: The coating composition prepared in the embodiment and the comparative example is applied on the diaphragm and cured to prepare a sample that meets the test standard specifications. The sample has a thickness of 2 um and is tested for peel strength after immersion in electrolyte at 80°C for 300 hours. The results are recorded in Table 1 as the average value of 10 tests, as well as the insulation properties of the tested product.
[0111] The coating compositions prepared in the examples and comparative examples were coated on the surface of the diaphragm with a thickness of 2 μm, and lithium batteries were manufactured. The capacity retention rate of the lithium batteries was tested, and the results were recorded in Table 1 as the average value of 10 tests.
[0112] Table 1
[0113]
[0114]
[0115] From the examples, comparative examples and the corresponding performance data results, it can be seen that the examples using the scheme defined in the present application can achieve better performance than the comparative examples in terms of stability, adhesion, insulation and capacity retention, and the performance of the product can be improved in a coordinated manner. In the comparative examples, comparative examples 1 and 5, no modified glass fiber and no regulating and stabilizing agent were added to the modified additives, and the performance of the product deteriorated significantly. The modified additives obtained by the coordinated combination of regulating and stabilizing agent and modified glass fiber have more significant product performance;
[0116] From Comparative Examples 2-4, Comparative Examples 6-7 and Example 3, it can be seen that
[0117] When modified titanium dioxide is not added in the modification of modified glass fiber, or titanium dioxide is used to replace modified titanium dioxide, the performance of the product shows a trend of deterioration. The modified glass fiber obtained by treating with the specific modified titanium dioxide of the present invention has the most significant product performance effect. At the same time, no bentonite is added in the preparation of the regulating and stabilizing agent, the bentonite agent is not prepared by first heating to 160°C at a rate of 2°C / min, keeping warm for 7.5 minutes, then heating to 220°C at a rate of 3.5°C / min, continuing to keep warm for 2 minutes, and finally air cooling to room temperature, and the bentonite agent is not prepared by yttrium nitrate solution, 2 parts of carboxymethyl cellulose and 3 parts of chitosan solution blended ball milling treatment, the performance of the products has a trend of deterioration. The regulating and stabilizing agent obtained by the method of the present invention has the most significant product performance effect, and the effects of other methods are not as obvious as those of the present invention.
[0118] In the lithium battery capacity retention performance test, the product was placed at 65°C for 48 hours to test the high temperature cycle stability of the product. The test results are shown in Table 2;
[0119] Table 2
[0120] Example Capacity retention rate (% 100 times) Example 1 99.0 Example 2 99.2 Example 3 99.4 Comparative Example 1 80.3 Comparative Example 2 83.5 Comparative Example 3 85.7 Comparative Example 4 73.2 Comparative Example 5 75.7 Comparative Example 6 82.4 Comparative Example 7 87.5
[0121] From the above performance tests, it can be seen that the products of Examples 1-3 have significant high-temperature cyclic stability effects, and the product performances of Comparative Examples 1-7 are not as significant as the product performance effects of Examples 1-3 of the present invention. At the same time, the inventors of the present invention found that when no bentonite agent was added in the preparation of the regulating stabilizer, the high-temperature cyclic stability effect of the product deteriorated significantly. At the same time, the raw materials of products prepared by different methods all have a significant trend of deterioration in product performance. Only the products prepared by the raw material method of the present invention have the most significant product performance effects. The products obtained by other methods are not as significant as the performance effects of the present invention.
Claims
1. An aqueous coating composition for a battery separator, characterized in that: The raw materials include, by weight: 15 to 25 parts of a binder, 1 to 10 parts of a swelling agent, 10 to 30 parts of a modifying additive, 0.5 to 5 parts of a cross-linking agent, 1 to 10 parts of an auxiliary agent, and deionized water added to 100 parts; The binder is a copolymer amine salt olefin resin; The copolymer amine salt olefin resin is at least one of ethylene-acrylic acid copolymer amine salt, styrene-ethylene-acrylic acid copolymer amine salt, styrene-acrylic acid-maleic anhydride copolymer amine salt, ethylene-methacrylic acid copolymer amine salt, and styrene-acrylic acid copolymer amine salt; The swelling agent is polyvinyl pyrrolidone or acrylic acid-vinyl pyrrolidone copolymer.
2. The aqueous coating composition for battery separator according to claim 1, characterized in that: The modified additive is a composition of modified glass fiber and a regulating stabilizer; The mass ratio of the modified glass fiber to the stabilizer is 7:(2-4); The preparation method of the modified glass fiber comprises the following steps: S1: 2-5 parts of urea, 1-3 parts of silane coupling agent KH560 and 4-7 parts of 10% by mass dodecylbenzene sulfonic acid solution are mixed to form a modified solution, 3-6 parts of titanium dioxide are added to the modified solution and stirred for modification treatment, the modification speed is 450-500r / min, the modification time is 1-2h, the modification temperature is 45-50°C, the modification is completed, washed with water, and dried to obtain modified titanium dioxide; S2: Dissolve 4-7 parts of succinic anhydride in 15-20 parts of DMF solvent, add 1-2 parts of (3-aminopropyl)triethoxysilane, then add 3-5 parts of modified titanium dioxide, heat and stir at a water bath temperature of 80-95°C for 1-2 hours, then cool to 60-70°C and keep warm for 2-3 hours, and collect the precipitate by centrifugation and washing; S3: Add the precipitate to a sufficient amount of ethanol, then add glass fiber, raise the temperature to 50-60°C, and stir in a water bath ultrasonic manner at a speed of 200-300 r / min and a power of 200-400 W for 3-4 hours, then centrifuge and wash, and vacuum dry at 60°C.
3. The aqueous coating composition for battery separator according to claim 2, characterized in that: The mass ratio of the precipitate to the glass fiber is (1-2):(8-12); The average length of the glass fibers is 1 to 3 μm.
4. The aqueous coating composition for battery separator according to claim 2, characterized in that: The preparation method of the regulating stabilizer comprises the following steps: S11: add 6-10 parts of bentonite to 25-30 parts of DMF solvent, perform water bath ultrasound at 100-200w for 1-2h, then add 1-3 parts of toluenesulfonic acid, raise the temperature to 50-60°C, and keep warm for 2-3h; S12; The product is washed by centrifugation and added to 15-20 parts of methanol, and 4-6 parts of dimethylimidazole and 2-4 parts of gas-phase alumina are added at the same time. The temperature is raised to 60-65°C and the reaction is carried out for 1.5-2h. After completion, the product is filtered and dried.
5. The aqueous coating composition for battery separator according to claim 4, characterized in that: The preparation method of the bentonite agent is: The bentonite is first heated to 155-165°C at a rate of 1-3°C / min, kept warm for 5-10 minutes, then heated to 210-230°C at a rate of 2-5°C / min, kept warm for 2 minutes, and finally air-cooled to room temperature. 5-10 parts of air-cooled room temperature bentonite, 2-5 parts of yttrium nitrate solution, 1-3 parts of carboxymethyl cellulose and 2-4 parts of chitosan solution are blended and ball-milled thoroughly. The ball-milling speed is 1000r / min. The ball-milling is carried out for 1 hour. After the ball-milling is completed, the mixture is washed with water and dried to obtain a bentonite agent.
6. The aqueous coating composition for battery separator according to claim 5, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the chitosan solution is 6%.
7. The aqueous coating composition for battery separator according to claim 1, characterized in that: The cross-linking agent is pentaerythritol-tris(3-aziridinyl)propionate.
8. The aqueous coating composition for battery separator according to claim 1, characterized in that: The auxiliary agents are defoamer and dispersant; the mass ratio of the defoamer to the dispersant is 1:1; the defoamer is BYK-019; and the dispersant is PEG-800.
9. A method for preparing an aqueous coating composition for a battery separator according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: S1: Add the binder into deionized water and stir evenly until there is no obvious floc; S2: Then add the modifying additive, swelling agent, cross-linking agent and auxiliary agent into the above S1 solution in sequence, stir and mix evenly, and ball-mill it thoroughly to obtain an aqueous coating composition for battery separators.